Innovative Learning Based on Focused Imaging in the Subject of Islamic Cultural History - Roihan Arrosyid; Faridi Faridi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
Learning Islamic Cultural History (SKI) or Tarikh often faces problems with low student participation and activeness. The problem largely lies in the use of conventional methods that are monotonous and boring. This study aims to design innovative learning based on focused imaging in SKI learning at SMP Muhammadiyah 10 Sidoarjo, which is expected to be a solution not only to increase participation and engagement, but also to improve contextual and problem-based understanding (Problem Based Learning). This method uses a qualitative approach of literature study, reviewing various relevant studies and studies to design innovative learning, and combined with case studies based on student situation analysis. The real implication is that students have the potential to understand history material better because they learn and collaborate in problem-based learning to find solutions and moral values. This innovative learning design uses the method from the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which requires two stages: needs analysis and learning planning. The results of the study describe an outline of innovative visual-based learning, depicting historical concepts concretely, and testing students to understand historical values through case study-based learning. The implication is that learning becomes more conceptual, interesting, and increases interaction between students.